Genome structure of caulobacter phage phiCb5 - Kazaks, Andris; Voronkova, Tatyana; Rumnieks, Janis; Dishlers, Andris; Tars, Kaspars (Journal of virology, 2011)
The complete genome sequence of caulobacter phage phiCb5 has been determined, and four open reading frames (ORFs) have been identified and characterized. As for related phages, the ORFs code for maturation, coat, replicase, and lysis proteins, but unlike other Leviviridae members, the lysis protein gene of phiCb5 entirely overlaps with the replicase in a different reading frame. The lysis protein of phiCb5 is about two times longer than that of the distantly related MS2 phage and presumably contains two transmembrane helices. Analysis of the proposed genome secondary structure revealed a stable 5' stem-loop, similar to other phages, and a substantially shorter 3' untranslated region (UTR) structure with only three stem-loops.